Patient and Provider Satisfaction With Telemedicine in Otolaryngology - Riley, Phoebe Elizabeth (OTO Open, 2021)
OBJECTIVE: The objective of this study is to evaluate patient and provider satisfaction with telemedicine encounters across 3 otolaryngology practices. STUDY DESIGN: Cross-sectional survey. SETTING: A military community hospital, an academic military hospital, and a nonmilitary academic center. METHODS: A telephone-based survey of patients undergoing telemedicine encounters for routine otolaryngology appointments was performed between April and July 2020. Patients were asked about their satisfaction, the factors affecting care, and demographic information. A provider survey was emailed to staff otolaryngologists. The survey asked about satisfaction, concerns for reimbursement or liability, encounters best suited for telemedicine, and demographic information. The results were analyzed with descriptive statistics and a multivariable logistic linear regression model to determine odds ratios. RESULTS: A total of 325 patients were surveyed, demonstrating high satisfaction with telemedicine (average score, 4.49 of 5 [best possible answer]). Patients perceived “no negative impact” or “minor negative impact” on the encounter due to the lack of a physical examination or face-to-face interaction (1.86 and 1.95 of 5, respectively). High satisfaction was consistent across groups for distance to travel, age, and reason for referral. A total of 25 providers were surveyed, with an average satisfaction score of 3.44 of 5. Providers reported “slight” to “somewhat” concern about reimbursement (40%) and liability (32%). CONCLUSION: Given patients’ and providers’ levels of satisfaction, there is likely a role for telemedicine in otolaryngology practice that may benefit patient care independent of the COVID-19 pandemic.